Kvalitative analyser og kvalitetssikring (Sociologisk Forskning, 2003)
Ensuring “qualitative quality": Tendencies in English and Scandinavian qualitative methodology literature.A research project concerning the quality of Danish qualitative interview investigations has been conducted at The Danish National Institute of Social Research in Copenhagen (Olsen, 2002a-c). In this article, selected parts of the project are presented. The main theme of the article is qualitative analyses and different - more or less competing - criteria for “qualitative quality”. The article is based on textual analysis of a wide range of English and Scandinavian qualitative methodology literature - approximately 200 books and articles - concerning qualitative analysis strategies, analytic induction versus deduction, coding and conceptualization, generalization and theory related versus theory generating qualitative analyses. In the article focus is also on how to ensure “qualitative quality” and its conceptual foundation. The article is concluded by the author presenting his own quality ensuring proposals.
Keywords: qualitative analysis; induction; deduction; coding; cunceptualization; generalization